2022
DOI: 10.1093/cvr/cvac152
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic cardiomyopathy: the need for adjusting experimental models to meet clinical reality

Abstract: Diabetic cardiomyopathy (CM), occurring in the absence of hypertension, coronary artery disease and valvular or congenital heart disease, is now recognized as a distinct, multifactorial disease leading to ventricular hypertrophy and abnormal myocardial contractility that correlates with an array of complex molecular and cellular changes. Animal models provide the unique opportunity to investigate mechanistic aspects of diabetic CM, but important caveats exist when extrapolating findings obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 271 publications
0
7
0
Order By: Relevance
“…The success rate of modelling in this experiment was similar to that of different breeds of pigs in other experiments, but hyperglycaemia was maintained for a longer time [ 16 , 18 ]. The heart anatomy and the electrophysiological characteristics of pigs are more similar to those of humans than rodents, making pigs an ideal animal model for simulating human heart disease [ 19 ]. However, previous studies have lacked longitudinal studies on cardiac function and structure in diabetic pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate of modelling in this experiment was similar to that of different breeds of pigs in other experiments, but hyperglycaemia was maintained for a longer time [ 16 , 18 ]. The heart anatomy and the electrophysiological characteristics of pigs are more similar to those of humans than rodents, making pigs an ideal animal model for simulating human heart disease [ 19 ]. However, previous studies have lacked longitudinal studies on cardiac function and structure in diabetic pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, inconsistencies regarding the potential of HFD to induce LV cardiac dysfunction remain, as different studies have failed to identify cardiac complications whereas others have shown structural remodeling and diastolic dysfunction [ 44 , 45 , 46 , 47 ]. These conflicting data presumably arise from differences in rodent strains, timing and duration of the dietary interventions and diet composition, also making comparison difficult and outcome variability higher [ 48 ]. In addition, preclinical studies on the HFD regime mainly fail to account for later systolic dysfunction or reduced EF [ 18 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, T2DM and its cardiovascular complications develop in a chronic manner most often in middle-aged or older adults [ 66 ]. Contrary to the clinical scenario, the majority of studies on diet-induced diabetic cardiomyopathy models last a few weeks and/or employ young rodents [ 48 ]. The little evidence regarding the chronic impact of diet on cardiometabolic outcomes emphasizes the need for preclinical investigation at different life stages.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients have a high prevalence of heart failure, termed diabetic cardiomyopathy, with rates between 19% and 26% [ 46 ]. This disease is often asymptomatic in early stages, first showing as a thickening of the left ventricular wall, causing isolated diastolic dysfunction [ 47 , 48 ]. Our study revealed that higher FIns levels, when genetically predicted, could notably increase the thickness of myocardial-wall thickness at end-diastole and regional peak circumferential strain, leading to changes in left ventricular characteristics, echoing prior studies [ 49 – 51 ].…”
Section: Discussionmentioning
confidence: 99%